Board capital and bank efficiency: Insight from Vietnam - Maria Kontesa; Esmie Obrin Nichol; Jia-Sing Bong; Rayenda Brahmana (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This study investigates the role of board capital on bank's efficiency for a sample of 45 banks in Vietnam over 2011-2015. Using robust panel regression, we find board capital is important in making Vietnamese bank efficient even after controlling its endogeneity issue. This study further documents that networking capital and experience capital are the important factors, but not education for bank efficiency. The findings of this research contribute to the entrenchment hypothesis in agency theory, where networking and experience can be the bargaining power for manager (agent) in securing their compensation. It also contributes to human capital theory and resource base view theory where it shows networking and experience are stratetic human capital resources for bank efficiency. The findings imply that shareholders should consider the networking and experience of board members during board elections. Future research may engage with the intervention of corporate governance monitoring or test it in other developing countries context.
Keywords: G21; G32; M12; 650; board capital; networking capital; education capital; experience capital; bank efficiency